Migration, gender, and farming systems in Asia: Evidence, data, and knowledge gaps - Mueller, Valerie; Kovarik, Chiara; Sproule, Kathryn; Quisumbing, Agnes R. (International Food Policy Research Institute, 2015)
This paper reviews the literature on migration in Asia, with specific attention given to how gendered migration may influence future agricultural productivity. The first section examines the current body of evidence on the state of international and internal migration, using large-scale datasets that cover several Asian countries. The second section summarizes the findings of an extensive literature review on gendered determinants of migration, employment, and remittances. The third section lays out the gains and losses of migration and discusses the evidence on possible changes in gender roles owing to migration.